2023
DOI: 10.1111/hel.12985
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR of string‐test collected gastric material: A feasible approach to detect Helicobacter pylori and its resistance against clarithromycin and levofloxacin for susceptibility‐guided therapy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…They demonstrated that there was a concordance rate of 95.9% between such a string-qPCR and 13 C-urea breath test, an accurate non-invasive method widely used in clinical practice for diagnosis of H. pylori infection. Moreover, they reported a high eradication rate of 91.8% with genotypic resistancetailored bismuth quadruple therapy [82]. The value of the string test coupled with RT-qPCR for detecting H. pylori resistance to clarithromycin and levofloxacin has also been validated in urban China in a recent multicenter, cross-sectional study [83].…”
Section: Novel Techniques For Collecting Specimens For Genotypic-base...mentioning
confidence: 99%
“…They demonstrated that there was a concordance rate of 95.9% between such a string-qPCR and 13 C-urea breath test, an accurate non-invasive method widely used in clinical practice for diagnosis of H. pylori infection. Moreover, they reported a high eradication rate of 91.8% with genotypic resistancetailored bismuth quadruple therapy [82]. The value of the string test coupled with RT-qPCR for detecting H. pylori resistance to clarithromycin and levofloxacin has also been validated in urban China in a recent multicenter, cross-sectional study [83].…”
Section: Novel Techniques For Collecting Specimens For Genotypic-base...mentioning
confidence: 99%